Succession planning, strategic flexibility as predictors of business sustainability in family-owned SMEs: Moderating role of organization improvisation - Ijaz Hussain Bokhari; Armanurah Binti Muhammad; Nazlina Zakaria (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The objective of the current study is to test the impact of succession planning (cognitive, structural, and relational ties), strategic flexibility, and organizational improvisation towards the business sustainability considering the triple bottom line as underpinning theory. The survey method was adopted for the data collection and structural modeling technique isused to test the hypotheses. The findings of the current study show that cognitive, structural, and relational ties indicate a positive and significant relationship with business sustainability. Furthermore, findings also indicate the positive and significant association between succession planning, strategic flexibility, organizational improvisation, and business sustainability. The result has shown that organizational improvisation moderates the relationship between succession planning, strategic flexibility, and sustainable business. However, the direction of the relationship between succession planning and sustainable business is positive while, in case of strategic flexibility and sustainable business are negative. Family-owned businesses need to consider succession planning particularly cognitive, structural, relational ties, and strategic flexibility to gain their business sustainability.
Keywords: 330; business sustainability; succession planning; strategic flexibility; organizational improvisation; sustainability; small and medium enterprises; SMEs